The Effect of Work-Life Balance, Telecommuting, Job Satisfaction, Sleep Duration, and Stress Management on the Physical and Mental Health of Overseas Workers in Jakarta - Muhammad Subhan Iswahyudi; Safrina Ramadhani (West Science Interdisciplinary Studies, 2023)
This study examined the effect of work-life balance, telecommuting, job satisfaction, sleep duration, and stress management on the physical and mental health of workers outside the Jakarta area. 400 workers were taken as samples in the survey, and regression analysis was used to analyze the data. Results showed that work-life balance, telecommuting, job satisfaction, sleep duration, and stress management were all significantly associated with physical and mental health. In particular, better work-life balance, telecommuting, job satisfaction, longer sleep duration, and effective stress management practices are linked to better physical and mental health. The findings suggest that organizations should prioritize policies and procedures that support work-life balance, telecommuting, job satisfaction, adequate sleep duration, and stress management to improve their workers’ physical and mental health.